Clinical outcomes and unmet therapeutic needs in new-onset refractory status epilepticus: evidence from a retrospective cohort - Clara Jünemann; Meike Menche; Marc Philipp Bergmann; Sascha Strehlau; Panagiota-Eleni Tsalouchidou; Joane Winkel; Ole J. Simon; Lena Habermehl; Katja Menzler; Patrick Schramm; Lars Timmermann; Susanne Knake; et al. (Neurological Research and Practice, 2026)
Abstract Background New-onset refractory status epilepticus (NORSE) is a rare, life-threatening condition occurring in individuals without prior epilepsy or acute structural, toxic, or metabolic causes. Its etiology often remains cryptogenic, and inconsistent terminology hampers early recognition and treatment. This study aims to better characterize NORSE to support faster clinical diagnosis and management. Methods We retrospectively identified all adult patients with status epilepticus (SE) admitted to the Department of Neurology, University Hospital Marburg, Germany, between 2011 and 2023. Demographic, etiologic, treatment, and outcome data from patients fulfilling consensus criteria for NORSE were compared with those of non-NORSE patients. We additionally performed a sensitivity analysis applying strict temporal diagnostic criteria (≤ 72 h) to assess the impact of consensus-based classification on cohort definition. Results Of 779 patients with status epilepticus, 120 fulfilled criteria for NORSE, delineating a distinct clinical subgroup characterized by advanced age and a female predominance (67.5%, p = 0.028). Phenotypically, NORSE was strongly associated with generalized seizure semiology (70.7%, p < 0.001) and a higher burden of nonconvulsive status epilepticus (45.8%, p < 0.001), while the underlying etiology frequently remained cryptogenic (56.7%). This constellation translated into an adverse clinical trajectory, reflected by reduced rates of discharge home, increased in-hospital mortality (19.5%, p < 0.001), and greater reliance on rehabilitative care. Notably, these differences were not paralleled by alterations in metabolic indices such as HbA1c or cholesterol, underscoring the limited discriminatory value of these parameters in NORSE. Application of strict temporal criteria resulted in a smaller, more conservative NORSE cohort, while key clinical features and outcomes remained largely unchanged. Conclusions NORSE defines a distinct and severe clinical syndrome within status epilepticus, characterized by older age, female predominance and adverse outcomes. Beyond the clinical severity of NORSE, our findings show that cohort composition is highly sensitive to the temporal operationalization of consensus criteria. Standardized application of diagnostic timing may therefore be essential for comparability across NORSE studies.